2015
DOI: 10.1177/0003122415596999
|View full text |Cite
|
Sign up to set email alerts
|

A Paper Ceiling

Abstract: In the early twenty-first century, women continue to receive substantially less media coverage than men, despite women’s much increased participation in public life. Media scholars argue that actors in news organizations skew news coverage in favor of men and male-related topics. However, no previous study has systematically examined whether such media bias exists beyond gender ratio imbalances in coverage that merely mirror societal-level structural and occupational gender inequalities. Using novel longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 104 publications
(115 reference statements)
4
54
0
7
Order By: Relevance
“…Shor, van de Rijt, Miltsov, Kulkarni, and Skiena (2015) found that "the more mentions a person receives today [in a newspaper], the larger the chances that this person is a man" (p. 968). Men who are mentioned in the news are often of high power and mentioned thousands of times; women are not mentioned to the same degree.…”
Section: Role Of the Mediamentioning
confidence: 99%
“…Shor, van de Rijt, Miltsov, Kulkarni, and Skiena (2015) found that "the more mentions a person receives today [in a newspaper], the larger the chances that this person is a man" (p. 968). Men who are mentioned in the news are often of high power and mentioned thousands of times; women are not mentioned to the same degree.…”
Section: Role Of the Mediamentioning
confidence: 99%
“…Mencionaremos una cuarta explicación presente en la literatura: el género de los tomadores de decisiones en las organizaciones de medios (Shor, Van de Rijt, Miltsov, Kulkarni & Skiena, 2015). Estas explicaciones se comentan a continuación.…”
Section: Marco Teórico Las Causas De Las Diferencias De Género En Cobunclassified
“…La cuarta posible explicación halla la razón de las diferencias de género en coberturas mediáticas en el género de trabajadores de medios, en especial de quienes toman las decisiones, tales como los directores y dueños de los medios de comunicación (Shor et al, 2015). De acuerdo con el Instituto Nacional de las Mujeres (2005, p. 14), los puestos directivos (dirección general, presidencia, vicepresidencia, asiento en consejo, etcétera) en las estaciones de radio mexicanas son ocupados por mujeres apenas en 12% de los casos.…”
Section: Marco Teórico Las Causas De Las Diferencias De Género En Cobunclassified
See 2 more Smart Citations